2006
DOI: 10.1681/asn.2005060586
|View full text |Cite
|
Sign up to set email alerts
|

Type IV Collagen Induces Podocytic Features in Bone Marrow Stromal Stem Cells In Vitro

Abstract: Bone marrow-derived stromal stem cells (BMSC) can differentiate along a variety of mesenchymal lines, including mesangial cells. For determining whether BMSC can be induced to differentiate along podocytic lines in vitro, canine BMSC were cultured on plastic, type I collagen, and NC1 hexamers of type IV collagen from normal and Alport canine glomerular basement membrane. Results were compared with a mouse podocyte cell line. In the case of the podocyte line, differentiation occurred on all three matrices as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
24
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 40 publications
3
24
0
1
Order By: Relevance
“…31 Immortalized podocytes also synthesize more ␣5(IV) collagen when cultured on NC1 hexamers of collagen IV purified from normal canine GBM. 32 Taking together all of the previous reports and our results presented here, there is now highly compelling evidence that podocytes synthesize GBM collagen ␣3␣4␣5(IV). However, the finding that collagen ␣1␣2␣1(IV) originates from both glomerular endothelial cells and podocytes, but collagen ␣3␣4␣5(IV) comes from podocytes alone, was unexpected.…”
Section: Discussionsupporting
confidence: 75%
“…31 Immortalized podocytes also synthesize more ␣5(IV) collagen when cultured on NC1 hexamers of collagen IV purified from normal canine GBM. 32 Taking together all of the previous reports and our results presented here, there is now highly compelling evidence that podocytes synthesize GBM collagen ␣3␣4␣5(IV). However, the finding that collagen ␣1␣2␣1(IV) originates from both glomerular endothelial cells and podocytes, but collagen ␣3␣4␣5(IV) comes from podocytes alone, was unexpected.…”
Section: Discussionsupporting
confidence: 75%
“…Other lines of evidence suggest that new podocytes may arise from bone marrow. [62][63][64] In this study, WT-1+PECs (parietal podocytes) were observed near the vascular pole in most glomeruli in children and adults, and some WT-1+cells were occasionally observed in the tunica intima and the tunica media of arterioles in the JGA. Whether any of these cells give rise to new podocytes deserves additional attention.…”
Section: Discussionsupporting
confidence: 49%
“…Similarly, in vitro co-culture of BMSC and podocytes treated with doxorubicin showed elevated endothelial growth factor and reduced injury in podocytes [17]. Another study indicates that BMSC undergo a degree of podocytic differentiation in vitro [46]. In another study [47] using a model of autosomally-recessive Alport syndrome mice, Prodromidi et al showed that a) an apparent podocyte phenotype was showed in mice transplanted with bone marrow, b) the podocyte defect was rectified and c) glomerular scarring and interstitial fibrosis were also significantly decreased.…”
Section: Discussionmentioning
confidence: 95%